Quality, safety and authenticity of insect protein-based food and feed: insights from the INPROFF Project - David Heath; Anja Vehar; Lenka Kouřimská; Martin Kulma; Petra Škvorová; Hana Šubrtová Salmonová; Barbora Lampová; Nayyer Rehman; Polona Jamnik; Barbara Jeršek; Matjaž Červek; Nataša Poklar Ulrih; et al. (Exploration of Foods and Foodomics)
This paper reviews the nutritional quality and safety of edible farmed insects from the point of view of the Czech-Slovenian bilateral project: Quality, Safety and Authenticity of Insect Protein-based Food and Feed (INPROFF). Insects as a sustainable source of dietary protein for animal feed and even humans, when integrated into the European agrifood system, could offer a solution to Europe’s feed protein deficit and help alleviate environmental pressure from increasing protein demand, such as declining availability of land, water, marine and energy resources, the overuse of pesticides and reduced biodiversity. However, despite a growing interest in the European Union (EU) in farming edible insects, many economic, scientific, technological, and social barriers remain. In response, Slovenia, represented by the Jožef Stefan Institute, the Biotechnical Faculty of the University of Ljubljana, and Jata Emona d.o.o. (the leading supplier of feedstuffs for the Slovenian market), a country with no history of insect rearing but an interest in alternative protein, joined with the Czech University of Life Sciences Prague, representing the Czech Republic—a country with a history of insect rearing and research into edible insects—to establish INPROFF a three-year bilateral project that aims to close the knowledge gap regarding the quality and safety of insect-based products and boost the farmed insect food and feed value chain. Specifically, it comprises three thematic pillars: (P1) nutritional enhancement, (P2) safety and quality and (P3) authenticity, traceability, and consumer acceptance. The paper also discusses the gaps in the metrological challenges of analysing insects, which will be critical for ensuring safety, quality, and sustainability. The paper finds that although much work has been done, many exciting avenues remain for new research.